Comparison of Social Engagement of Children Having Disabilities with Their Mothers and Fathers - KARAASLAN, ÖZCAN (EDAM, 2016)
This study examined differences between mothers' and fathers' style of interaction and engagement with their preschool-aged children with Down syndrome (DS) and autism. Data was collected from a sample of 27 mother-child and 27 father-child dyads in which all the children were diagnosed with DS or autism. Participants were both parents and their children from the same family, which allowed comparisons between the mother and father of the same child. Both parents with their children were video recorded during free-play time with a set of developmentally appropriate toys. All video recordings were analyzed with the Turkish versions of the Maternal Behavior Rating Scale and Child Behavior Rating Scale. Findings revealed that Turkish mothers of children with DS and autism are more responsive than fathers. Additionally, fathers of children with DS scored higher on responsiveness and affect as well as attention and initiation but scored lower on achievement/directive. Both mothers and fathers interact better with children with DS than children with autism in terms of responsiveness associated with the child's social engagement. Results also indicated that, regardless of whether the child had DS or autism, both the mother's and father's level of responsiveness was associated with the child's engagement.
Keywords: Autism; Down syndrome; Children's social engagement; Interaction of mother-child and father-child; RELATIONSHIP FOCUSED INTERVENTION; MATERNAL RESPONSIVITY PREDICTS; YOUNG-CHILDREN; TURKISH MOTHERS; LANGUAGE; PARENTS; SKILLS; PLAY; DIRECTIVENESS